2015
DOI: 10.1142/s0219887815500851
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse in gravity's rainbow

Abstract: In this paper, we will analyze the gravitational collapse in the framework of gravity's rainbow. We will demonstrate that the position of the horizon for a particle inside the black hole depends on the energy of that particle. It will also be observe that the position of the horizon for a particle falling radially into the black hole also depends on its energy. Thus, it is possible for a particle coming from outside to interact with a particle inside the black, and take some information outside the black hole.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…[4]. Other consequences of the gravity's rainbow in the context of the gravitational collapse and black hole physics have been investigated in literature (see [5][6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…[4]. Other consequences of the gravity's rainbow in the context of the gravitational collapse and black hole physics have been investigated in literature (see [5][6][7][8] and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…It may be noted that the idea that the geometry of spacetime appear different for an in-falling observer and an asymptotic observer has been made for discussing the black hole complementarity [97,98,99,100]. It has been observed that the gravity's rainbow also modifies the geometry of a black hole, and this modification has been used to address the black hole information paradox [101,102,103]. It may be noted in the commutative limit these corrections vanish, and we obtain the original case back.…”
Section: New Noncommutativity For Black Holesmentioning
confidence: 99%
“…In [30], the gravitational collapse is analyzed in the context of gravity's rainbow [31]. The rainbow gravity is basically a possible step towards repairing the rifts between the theories of general relativity and quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%